Older Adults in the Participatory Design of Learning Experiences Involving Information and Communication Technologies - Castro-Rojas, María Dolores (2025)
This article examines the participation of older adults (OAs) in a participatory design (PD) workshop aimed at improving a learning intervention mediated by information and communication technologies (ICTs). The study follows a qualitative, descriptive approach within the framework of participatory design. The primary data collection method was a participatory design workshop that included both individual and group activities, as well as written and oral design suggestions. The workshop took place four months after the completion of the learning intervention and involved 20 older adults who had previously participated in the program. The workshop activities and results were documented through audio and video recordings, as well as written materials, including participants’ contributions and researchers’ field notes. All collected data were transcribed and analyzed using thematic analysis. Participants actively engaged in the workshop, with most understanding the assigned tasks and providing suggestions to improve the learning activities. Their recommendations primarily focused on familiar  aspects, while fewer contributions addressed more novel or creative elements. Only a small number of participants encountered difficulties in understanding the instructions or formulating improvement suggestions. The findings highlight the importance of employing diverse co-design techniques and materials to accommodate the varying skills, experiences, and interests of participants. Additionally, involving older adults in all stages of the design process can enhance their familiarity with the role of co-designers and strengthen their ability to contribute meaningful and critical insights.